Pelayanan Publik Berbasis Teknologi Informasi di Kelurahan Semarapura Kaja - Anak Agung Ayu Dewi Larantika; Ni Made Jaya Senastri; I Made Suniastha Amerta; A. A. Istri Pradnyarani Dewi (Universitas Warmadewa, 2021)
Advances in technology provide convenience in the implementation of public services in the global era. Ease in public services, among others, by providing facilities that facilitate the process of public service itself, such as the management of various certificates related to the needs of the community in Semarapura Kaja Village. The problem is that there is no system at the kelurahan level that makes it easier for the community to administer a residence certificate. The method of activity in this case is making application for certificate management and socialization as well as assisting the use of applications in managing population certificates in the village. The output of this activity is an application for managing a residence certificate and optimal use of information technology by the people of Semarapura Kaja Village as a form of implementing public services.